Development of a computer aided manufacturing management information systems at Mitsubishi Electric Malaysia Sdn Bhd in process planning - 266908 Go, Ching Lian (Sekudai: UTM, 1992)
Work-in-progress inventory is the major problem faced by batch type of production system. Fall of monitoring this inventory could lead to deficiency of inventory management. The purpose of this project is to develop an information system for the use of A.I. Department, MITSUBISHI ElECTRIC MALAYSIA, in the area of work-in-progress monitoring. This project outlined all the development processes from data collection stage to implementation stage. The system analysis was used to gather user requirements. Each stage of the project is described in great detail in separate chapters in this thesis. The approaches and view used in developing this package is the combination of production control function and information system requirement. The system had been implemented in A.I. Department and the result is encouraging in term of timeand cost saved. The system capable of generating various type of reports. Among them are status report., insertion point report and etc. The system had been customized fully and completely for this enviroment. This package was developed using dBASE IV, one of the most widely used database management language.